Rhythmic Physical Activity Intervention: Exploring Feasibility and Effectiveness in Improving Motor and Executive Function Skills in Children - Vazou, Spyridoula; Klesel, Brenna; Lakes, Kimberley D.; Smiley, Ann (Frontiers in Psychology, 2020)
Increasing literature has emerged investigating the importance of considering the qualitative characteristics of PA interventions and sports as well as considering the role of motor competence in the exercise-cognition interplay. The purpose of this pilot study was to examine the feasibility and effectiveness of a rhythmic PA intervention, compared to a standard physical education (PE) program, on motor, hot, and cool Executive Function (EF) skills. Methods. Children ages 6 to 11 were enrolled in one of the two programs: a rhythmic program (n= 22) and a physical education program (n= 17), both meeting for 30 minutes, twice per week, for 7 weeks. The rhythmic program emphasized moving to the beat of music and moving in various rhythmic patterns with whole body movements, clapping, and drumsticks. The children also created their own rhythmic patterns and socially engaged with other children by working in pairs and sharing their routines with the group. The physical education group engaged in ball skills, locomotor patterns, team sports, and moving through stations in small groups, with no emphasis on rhythm. Pre- and post-test measurements included measurement of balance (Movement ABC-2), cool and hot EF (Flanker, SWAN), and social factors, whereas throughout the implementation period data on affective valence, enjoyment, cognitive engagement, perceived exertion, and PA levels were collected at every lesson in both groups. Results. The rhythmic program used in this study was feasible, scalable, affordable, and able to be implemented with minimal preparatory time. Children in both groups (rhythmic and PE) engaged in a similar level of PA and had similar positive experiences from the programs. Both groups improved in balance and cool EF, and there were significant correlations in the change-scores between balance and cool EF, as well as between cool EF with hot EF and socio-emotional factors. Discussion. This study contributes to the literature by exploring the potential value of rhythmic programs as a vehicle in helping children develop motor and EF skills while deriving joy and positive social interactions from the program.